Multi‐drug resistance in Streptococcus pneumoniae among children in rural Vietnam more than doubled from 1999 to 2014. (15th February 2021) - Larsson, Mattias; Nguyen, Hoa Quynh; Olson, Linus; Tran, Toan Khanh; Nguyen, Trung Vu; Nguyen, Chuc Thi Kim
Abstract: Aim: This study assessed the Streptococcus pneumoniae colonisation rate and susceptibility to antibiotics among preschool children in rural Vietnam. Method: Nasopharyngeal samples were collected from 546 preschool children aged 6–59 months living in 460 households in the rural BaVi District of Hanoi and their main caregivers completed questionnaires. The samples were cultured, and the Streptococcus pneumoniae colonisation rate and antibiotic susceptibility were investigated. Resistance data from this 2014 study were compared with studies in 1999 and 2007, to identify 15‐year trends, together with clinical isolates from a national surveillance system of 16 Vietnamese hospital laboratories established in 2013. Results: We found that 221/546 (40%) of the cultures were positive for Streptococcus pneumoniae . The susceptibility rates were trimethoprim‐sulphamethoxazole (5%), erythromycin (8%), ciprofloxacin (12%), benzyl‐penicillin (35%), tetracycline (49%), cefotaxime (55%), moxifloxacin (99%) and vancomycin (99%). All the susceptibility rates were lower in 2014 than 1999 and 2007, except tetracycline. Multi‐drug resistance was 80% in 2014, compared to 60% in 2007 and 31% in 1999. Antibiotics was reported used by 191 (35%) within one month, mainly cephalosporins 86 (45%), amoxycillin/ampicillin 69 (36%) and macrolides 30 (16%). Conclusion: Streptococcus pneumoniae showed remarkable high resistance to commonly used antibiotics, including cephalosporins. Multi‐drug resistance rose from 31% to 80% during the 15‐year study period.